INVESTIGATING THE POSSIBLE MEASURES TAKEN TO OVERCOME INTERPERSONAL COMMUNICATION BARRIERS BETWEEN PARENTS AND THEIR YOUTH ON HIV PREVENTION - Okongo, Pamela Abonyo (IJRDO- Journal of Educational Research, 2020)
The study examined the influence of parent and youth interpersonal communication barriers on HIV prevention in North Kamagambo Location, Migori County. The study covered a population of 18,755 according to the 2009 National Census Report. The specific objective of this study was to identify the possible measures that should be taken to overcome IPC barriers between parents and their youth on HIV prevention and how these measures can curb the spread of HIV among youth of North Kamagambo Location. The study was informed by literature that supports the presumption that youth rarely communicate with their parents on matters of HIV AIDS  this thus increases their vulnerability. The study applied Social Learning Theory and Health Belief Model to demonstrate how the youth can learn from their parents through modeling. Qualitative method was used to interpret social interaction and emphasis was on words, coding and themes while Quantitative method was used to analyze the frequency of occurrence of these thematic elements. Stratified sampling was used to sample the entire population into different sub groups or stratum i,e between 12-30 youth age and between 30-50 parent age.Simpe random sampling was used to select a minimum of two hundred and forty respondents (240) of whom 80 respondents were for in-depth interview and one hundred and sixty(160) were for focus group discussion.Finding stated that, 50% of respondents strongly agreed that persuasive IPC help to educate the youth to change their behavioral attitude on sexual activities to produce a substantial and lasting reduction on HIV transmission. While 56.25% of respondents were neutral they were neither positive nor negative quite unstable in their feelings.  The study recommends high quality youth health materials available in all languages that young people in the community speak and for various reading levels including low literacy.